Animals in a long dream series - Schredl, Michael (International journal of dream research, 2021)
Animals are found quite often in dreams and speculations about their meanings are manifold. The present study is based on a series of 8,420 dreams of a young male. Overall, animals were present in about 7% of them. Specific waking-life experiences of the dreamer such as living with cats or having had a pet hamster are reflected in his dreams. On the other side, the negative animal contacts with snakes and spiders are not continuous with his waking life and might reflect continuity on an emotional level. In order to confirm this and other hypotheses, studies eliciting the amount of contact to real animals during daytime, media exposure to animals, whether the person is especially fond of specific species, and current emotional issues should be carried out in order to study the effect of these variables on the frequency of animal dreams.